Complete assignment of All C-13 NMR signals of C-s symmetric monoazafullerene derivatives by comparison of experimental and calculated Spektra - Hauke, Frank; Chen, Zhongfang; Hirsch, Andreas (Polish Journal of Chemistry, 2007)
The complete assignment of all 31 (CNMR)-C-13 signals which are due to the fullerene carbon atoms of monoazafullerene derivatives has been carried out for the first time by the systematic comparison of experimental and theoretical spectra calculated by high level DFT methods (GIAO-B3LYP/6-31G*/B3LYP/6-31G*). The assignment is facilitated by the striking similarities of the signal patterns of the sp(2)-fullerene carbon atoms of two different families of such heteroftillerene derivatives with both aryl and alkyl addends.
Keywords: fullerene; heteroftillerene; NMR spectroscopy; DFT calculation; chemical shift